2021
DOI: 10.1038/s41380-021-01269-w
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic changes in animal models of depression: a systematic analysis

Abstract: Extensive research has been carried out on the metabolomic changes in animal models of depression; however, there is no general agreement about which metabolites exhibit constant changes. Therefore, the aim of this study was to identify consistently altered metabolites in large-scale metabolomics studies of depression models. We performed vote counting analyses to identify consistently upregulated or downregulated metabolites in the brain, blood, and urine of animal models of depression based on 3743 different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(30 citation statements)
references
References 61 publications
3
27
0
Order By: Relevance
“…Moreover, we found that these altered amino acid neurotransmitters enriched in the amino acid metabolism pathway of taurine and hypotaurine metabolism, phenylalanine metabolism, and glutathione metabolism. These results are in line with the findings of a systematic analyse that indicated abnormalities of amino acid neurotransmitters in depression models (Pu et al, 2021).…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, we found that these altered amino acid neurotransmitters enriched in the amino acid metabolism pathway of taurine and hypotaurine metabolism, phenylalanine metabolism, and glutathione metabolism. These results are in line with the findings of a systematic analyse that indicated abnormalities of amino acid neurotransmitters in depression models (Pu et al, 2021).…”
Section: Discussionsupporting
confidence: 90%
“…Reviews of depression indicate at least five major biological systems are involved in depression, namely, inflammation, neuroendocrine, neurotransmitter, growth factor, and metabolic (Strawbridge et al, 2017;Zwolinska et al, 2021); biomarkers in these areas have been investigated using many approaches, including genetics (Flint and Kendler, 2014), epigenetics (Dalton et al, 2014), metabolomics (Bot et al, 2020), and the gut microbiome (Qin et al, 2022). Metabolomic investigations have been used in studies of somatic health conditions for many years and have more recently been used in psychiatry (Martins-de-Souza, 2014;Guest et al, 2016;Bot et al, 2020;Pu et al, 2021). Metabolomic approaches--in particular untargeted approaches, which use a broad panel of metabolite information to investigate associations--have been harnessed to generate new ideas and hypotheses in mental health (Bot et al, 2020;Whipp et al, 2021b), and continue to be useful in studies of depression.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, vote counting is an effective method for selecting molecules to be independently validated by external studies, with the assumption that a reliable differential molecule is robust enough to show significance across multiple studies [ 30 ]. This approach has been recently implemented in other research integrating large-scale metabolomics studies [ 31 , 32 ].…”
Section: Methodsmentioning
confidence: 99%